Search for RR Lyrae stars in DES ultrafaint systems : Grus I, Kim 2, Phoenix II, and Grus II - Martínez-Vazquez, Clara Eugenia (2019)
This work presents the first search for RR Lyrae stars (RRLs) in four of the ultrafaint systems imaged by the Dark Energy Survey using SOAR/Goodman and Blanco/DECam imagers. We have detected two RRLs in the field of Grus I, none in Kim 2, one in Phoenix II, and four in Grus II. With the detection of these stars, we accurately determine the distance moduli for these ultrafaint dwarf satellite galaxies; μ0 = 20.51 ± 0.10 mag (D⊙ = 127 ± 6 kpc) for Grus I and μ0 = 20.01 ± 0.10 mag (D⊙ = 100 ± 5 kpc) for Phoenix II. These measurements are larger than previous estimations by Koposov et al. and Bechtol et al., implying larger physical sizes; 5 per cent for Grus I and 33 per cent for Phoenix II. For Grus II, of the four RRLs detected, one is consistent with being a member of the galactic halo (D⊙ = 24 ± 1 kpc, μ0 = 16.86 ± 0.10 mag), another is at D⊙ = 55 ± 2 kpc (μ0 = 18.71 ± 0.10 mag), which we associate with Grus II, and the two remaining at D⊙ = 43 ± 2 kpc (μ0 = 18.17 ± 0.10 mag). Moreover, the appearance of a subtle red horizontal branch in the colour–magnitude diagram of Grus II at the same brightness level of the latter two RRLs, which are at the same distance and in the same region, suggests that a more metal-rich system may be located in front of Grus II. The most plausible scenario is the association of these stars with the Chenab/Orphan Stream. Finally, we performed a comprehensive and updated analysis of the number of RRLs in dwarf galaxies. This allows us to predict that the method of finding new ultrafaint dwarf galaxies using two or more clumped RRLs will work only for systems brighter than MV ~−6 mag.